Repeated pregnant mare serum gonadotropin‐mediated oestrous synchronization alters gene expression in the ovaries and reduces reproductive performance in dairy goats. Issue 6 (3rd May 2019) - Sun, Shuang; Liu, Shimin; Luo, Jun; Chen, Zhi; Li, Cong; Loor, Juan J.; Cao, Yanhong
Contents: This study aimed to elucidate the effects of repeated pregnant mare serum gonadotropin (PMSG) treatment for oestrous synchronization (ES) on ovarian gene expression and reproductive parameters in Xinong Saanen dairy goats, the dominant breed of dairy goat in China. The experiment was carried out at the Research Station of Northwest A&F University (NWAFU), China (34°16′N, 108°4′E). Forty‐one does were randomly assigned to groups receiving ES treatments thrice every fortnight (3‐PMSG group; n = 19), or ES treatment only once simultaneously with the third ES treatment in the 3‐PMSG group (1‐PMSG group; n = 22) during middle of the breeding season from late July (14 hr light) until late September (12 hr light). ES treatment was performed via intravaginal insertion of a controlled internal drug release (CIDR) device impregnated with 300 mg progesterone (P4), followed by 300 IU PMSG injections 48 hr before CIDR withdrawal. Oestrus was monitored using vasectomized bucks. Ovaries of three goats in oestrus from both groups were harvested for morphological examination and RNA sequencing (RNA‐Seq). Then, all the oestrous goats in the 1‐PMSG ( n = 21) and 3‐PMSG ( n = 11) groups were artificially inseminated twice. The 3‐PMSG group showed reduced oestrous rate (57.89%), pregnancy rate (31.58%) and litter size (1.17) compared, respectively, with 95.45%, 68.18% and 1.67 for 1‐PMSG group ( p < 0.05). However, no differences were found in the ovarian morphology between the 1‐PMSG and 3‐PMSG groups ( p > 0.05). RNA‐Seq revealed 114 differentially expressed genes (DEGs) in the ovaries of the 3‐PMSG group, among which GCG, FSTL3, TET3 and AQP3 were deemed novel and promising candidate genes for regulating fertility. The present study indicates that the three‐time PMSG treatment dysregulated several ovarian genes, thereby reducing reproductive performance.